PEMANFAATAN ASAP CAIR DARI PIROLISIS CANGKANG KELAPA SAWIT SEBAGAI PENGAWET ALAMI TAHU (Talenta Publisher (Universitas Sumatera Utara), 2015)
This research aims to utilize the coconut-palm shell waste to be processed as liquid smoke grade I, used for natural preservative of tofu. The process used to produce the liquid smoke is by using pyrolysis method. The pyrolysis temperatures used ware 300 oC, 340 oC, and 380oC, with liquid smoke concentration of 0.5%, 1%, 2%, 4%, and 6%. Purification of liquid smoke from grade III to grade I was made through two distillation phases at temperature of 200 oC. The produced liquid smoke grade I was then utilized to preserve the tofu in order to increase its storing period. The testing towards durability of the preserved tofu was done by Total Volatile Base (TVB) and Organoleptic. Based on the TVB values test, the tofu can last for 56 hours when it was soaked in liquid smoke, while the durability of the tofu without soaked in liquid smoke was only 16 hours. Results of the organoleptic test showed that 90% of respondents favor the taste, flavor, and texture of the liquid smoke-soaked tofu, which was pyrolysed at 340oC and at concentration of 0.5%. the TVB Value at these condition was 19.61mg N%.